Quantifying the effects of non-tariff measures on African agri-food exporters. Issue 4 (2nd October 2019) - Liu, Chang; Lin, Dongtao; Liu, Jiawei; Li, Yanran
ABSTRACT: Non-tariff measures (NTMs) such as technical barriers to trade (TBT) and sanitary and phytosanitary measures (SPMs) have become new trade barriers, which is contrary to these measures' original intention to correct market failure and adverse selection of free markets and to protect the people, animals, plants and the environment in importing countries. For different African agri-food exporters, the compliance with NTMs has varied impacts. For relatively comprehensive exporters, NTMs are helpful in upgrading their food production, increasing agricultural input and promoting sustainable development. For countries with relatively less diversified crops, however, such compliance has huge negative effects such as rise in trading costs and reduction in exporting profits. In an attempt to address the above-mentioned issue using the VARMA(X) model and intervention analysis, this paper first examines agri-food trade records between African countries and analyses NTMs, which reveals the mechanisms of NTMs. Second, defining impacts of NTMs as the difference between the estimated agri-food trades' volumes between African countries from 1996 to 2013 without NTMs and the actual volumes, the paper shows that NTMs have in fact led to a significant reduction in agri-food trade volume in Africa. Finally, based on these empirical econometrical results, the authors suggest possible solutions, including strengthening external assistance, improving trade liberalisation and accelerating economic integration.